Java 9 Programming Blueprints - Lee, Jason (Packt Publishing Limited, 2017)
bBuild a variety of real-world applications by taking advantage of the newest features of Java 9/bh2About This Book/h2ulliSee some of the new features of Java 9 and be introduced to parts of the Java SDK/liliThis book provides a set of diverse, interesting projects that range in complexity from fairly simple to advanced and cover HTTP 2.0/liliTake advantage of Java's new modularity features to write real-world applications that solve a variety of problems/li/ulh2Who This Book Is For/h2This book is for Java developers who are already familiar with the language.